Micro Strategies for Higher Education Attendance and Assessment - Aurora, Rajinder S.; Shetty, Kavita (SFIMAR Research Review, 2016)
Higher Education in India is undergoing a paradigm shift with many innovative changes being introduced. Some changes are called for due to the changing environment like anti-ragging and sexual harassment policies, changing perception of the younger generation; while some changes are thought of as an essence to innovation and redefining strategies like changes in teaching pedagogy and assessment and evaluation mechanism. This paper looks at the issue of attendance monitoring for the teachers and students alike. The paper is based on the hypothesis that monitoring the attendance is critical to improving the work environment and promotes effectiveness in teaching and learning. The paper also explores the issue of assessment. This has always been a very debatable issue of higher education since it is subjective and often involves unethical practices. A/so the objections and doubts raised by students on the validity of the process puts a question mark on how authentic the process is. The hypothesis made by the authors in this respect is that the present system is far from being fool-proof and needs drastic changes so that it is accepted by the teachers and students alike. While these suggestions are being made they are subject to lot more debate and discussion, since individual thoughts and perceptions would still differ. The authors have used a questionnaire to seek answers to these debatable issues and arrived at their conclusions based on the response received to the questionnaire.